Experiences of using a digital tool, the D‐foot, in the screening of risk factors for diabetic foot ulcers - Roland Zügner; Gustav Jarl; Leif Sundberg; Ulla Hellstrand Tang (Journal of Foot and Ankle Research, 2022)
Abstract Background Individuals living with diabetes run an increased risk of developing diabetic foot ulcers (DFUs), leading to high costs to society and reduced quality of life for the individual. Regular screening is important to avoid complications. Aim To evaluate patients' and clinicians' experiences of using a digital tool, the D‐Foot, in the screening of risk factors for developing DFUs. The secondary aims were to investigate whether patients had had their feet examined by a nurse or doctor during the past year, had been referred to podiatry and whether patients had received information about self‐care. Methods A prospective study was carried out, comprising 90 patients with diabetes visiting a Department of Prosthetics and Orthotics (DPO). Two Certified Prosthetists and Orthotists (CPOs) were included, and they assessed foot status and the risk of developing DFUs with the D‐Foot software, prior to prescribing footwear. The quality of services at the DPO was assessed by the patients using the Orthotics and Prosthetics Users' Survey (OPUS). The CPOs answered the System Usability Scale (SUS) before and after the study to assess the usability of the D‐Foot. Results No patient had risk grade 1. One (1%) patient had risk grade 2, 78 (87%) patients had risk grade 3 and 11 (12%) patients had risk grade 4. Patients reported high levels of satisfaction on eight of ten OPUS items and the two items with lower scores were not related to the use of the D‐Foot. The two CPOs reported levels above the mean regarding usability both before (77.5 and 90) and after (70 and 97.5) using the D‐Foot. Conclusions Patients expressed a high level of satisfaction with the services when their feet were examined with the D‐Foot prior to the provision of footwear. The CPOs found that the D‐Foot system was usable. Several comments were made by patients and CPOs and will support the future development and testing of the D‐Foot. There is a need to increase referrals for preventive podiatry and improve information on self‐care for patients at risk of DFUs. Trial registration ClinicalTrials.gov ID: NCT04054804.